The current status of environmental reporting by Indian companies - Chatterjee, Bikram; Zaman Mir, M. (Emerald Group Publishing Limited, 2008)
Purpose – The purpose of this paper is to explore the state of environmental reporting by Indiancompanies on their web sites and also in their annual reports.Design/methodology/approach – The web sites of the companies in the sample were visited toexamine the accessibility and extent of environmental information disclosure on their web sites. Theannual reports for 2003-2004, as available on the companies’ web sites were selected to investigate theextent of environmental information disclosure in these annual reports.Findings – The paper finds that, although there are no regulations enforcing the disclosure ofenvironmental information, most of the Indian companies have disclosed environmental information.These companies provided more environmental information on their web sites compared to theinformation provided in their annual reports.Originality/value – This study contributes to the existing body of environmental reportingliterature by focusing on the status of environmental reporting by companies of an emerging economyand also contributes to the existing body of environmental reporting literature by focusing on theaccessibility of environmental information on web sites of respective companies.